The impacts of polystyrene microparticles in the fatty acids and carbohydrate composition of the commercial bivalve species Scrobicularia plana - Tagliaferro, Marina Beatriz (2020)
Estuaries are one of the most important ecological and socio-economic ecosystems. Estu-aries are hotspots of microplastic pollution. Scrobicularia plana, an infaunal benthic bivalve,is one of the most abundant invertebrates, with an important role in estuarine trophic foodwebs and is also very appreciated by humans as food source, owning a great economic value.The aim of this study was to determine the potential impacts in the fatty acid (FA) andcarbohydrates (CHO) content and thus on the quality of S. plana exposed to increasingconcentrations of polystyrene microparticules (1 m; MP). We used two bivalves' size classes(small; big) and exposed to 0.00, 0.25, 2.5 and 25 g/L of the MP. Results show changes onFA and CHO proles among both size classes of S. plana when exposed to polystyrene treat-ments. At the big individuals the content of saturated FA increased, and monounsaturatedFA decreased with increasing MP concentration. At small organisms, monounsaturated FAincreased from low to high MP concentrations. High unsaturated FA decreased from low tohigh MP concentrations (2.5 g/L and 25 g/L at small and big size classes respectively).The most abundant CHO was glucose for both size classes. In big size organisms, Rhamnoseand Arabinose increased with increasing of polystyrene concentration. In big organisms CHOchanges from control to MP treatments. In small size individuals, CHO content was simi-lar among 0.0 to 2.5 g/L but increased at the highest MP concentration. Results suggestS. plana big size class is more aected by polystyrene microparticles with a stronger eecton CHO prole, whereas both size classes decreased in FA quality when exposed to higherpolystyrene concentrations. This study highlights the eects of polystyrene in edible bivalvespecies and thus on human diet and health.